The Impact of Chinese City Tour's Restorative Servicescape on Tourist Satisfaction : Focusing on the Mediating Effect of Perceived Values - Sun, XiaoLi (International Theory and Practice in Humanities and Social Sciences, 2025)
A study of this paper is to analyze how Chinese tourists perceive factors of restorative servicescape in China, and how restorative servicescape impacts tourist satisfaction. The results of the study were as follows: First, restorative servicescape had a significant positive effect on perceived values. Second, servicescape had a significant positive effect on satisfaction. Third, perceived values had a significant positive effect on satisfaction. On the other hand, 'coherence' affects 'satisfaction' in a negative direction. Thus, hypothesis 1 was partially adopted in the results of verifying the mediating effect of the perceived values in the influence of the restorative servicescape on the tourist satisfaction, the 'being away', 'fascination' 'coherence' and 'compatibility', which are the sub-factor of the restorative servicescape, were represented to have effect on the tourists satisfaction through the mediating effect of the monetary valves, emotional values and the social values, which are the sub-factor of the perceived values. By determining the effect of the Chinese city tour visitors' perceived restorative servicescapes on the satisfaction, the following research contributes to providing solutions that allow visitors to have a positive perception on the service environment of city tour. Furthermore, with regard to the service environment development and management, the results of the study suggest effective and efficient developing strategies that enable the city tour in China to build a competitive advantage.